The Influence of Flexible Work Arrangements on the Corporate Efficiency During the Covid-19 Pandemic in the Republic Of Serbia - Gašić, Dimitrije (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
The author investigates the impact of the application of flexible work arrangements on the corporate efficiency of companies during the COVID - 19 pandemic in the Republic of Serbia. The main question is whether the application of flexible work arrangements has a positive impact on the efficiency of the corporation, its employees and how their application affects the business of companies in the current situation that has not passed any business sector around the world. Motivation: Based on the study by authors such as Bhattacharya et al. (2005), Austin-Egole et al. (2020), Berber & Slavi? (2019), the author plans to identify the impact of flexible work arrangements on corporate efficiency. The idea for the research arose due to the change in the way of doing business and the increasing application of flexible work arrangements in the modern business of almost every company around the world due to the outbreak of the COVID -19 pandemic. Data: The research was conducted at the end of 2020. and the beginning of 2021. on a sample of 219 employees who were greatly influenced by this pandemic in the business itself, which largely differs from the previous one. Data collection was done through an electronic questionnaire Google-Forms, based on which employees had the opportunity to answer questions with their electronic devices at any time, which is a great advantage especially in today’s lifestyle where everything has become mobile and internet access enabled at any time wherever you are. Tools: To analyze the collected data, the SPSS (The Statistical Package for the Social Sciences) program was used. In his work, the author applied the following data processing techniques: T-test of independent samples, One-way ANOVA, and Spearman correlation. Findings: Based on the conducted research, the results indicate a positive relationship between flexible work arrangements and employee productivity. Contribution: The paper contributes to the literature by empirically examining the impact of certain factors on corporate efficiency and thus on the company’s success in the Republic of Serbia during the COVID - 19 pandemic.